A Comprehensive Analysis of Energy Security in the Member States of the Eurasian Economic Union, 2000-2014 - Bogoviz, Aleksei Valentinovich; Lobova, Svetlana Vladislavlevna; Ragulina, Yulia Vyacheslavovna; Alekseev, Alexander Nikolaevich (International Journal of Energy Economics and Policy, 2017)
The article analyzes how well the countries of the Eurasian Economic Union (EAEU) are doing in terms of energy security. This research relies on a comprehensive concept of energy security that distinguishes the total of four dimensions of energy security: availability, affordability, efficiency, and environmental stewardship. We construct an energy security performance index in order analyze the relative energy security performance of the EAEU countries. The index is composed of ten indicators, and each of them reflects a certain dimension of energy security. We evaluate the relative energy security performance of the whole union and each country individually from 2000 to 2014. Our analysis shows that the EAEU energy security is quite low due to countries’ diverse energy security performance. Keywords: Energy Security, Eurasian Economic Union (EAEU), Security of Supply JEL Classifications: Q2, Q3, Q4